Promoting audiovisual insights in math subjects - Soares, Filomena (2018)
It seems that the digital world is all around us, wherever we turn to. Although not palpable, this world is already an important part of our everyday lives. When we talk specifically about the teaching/learning process we see that, at least in the last decade, the development of alternative and new strategies has been huge. The way students react to some methods and tactics is changing and engaging them in their own learning process is becoming a constant “challenge” to teachers, in all different educational levels. As Math professors in a High Education Institution where Mathematics is a basic and supporting course to other advanced (but non-Mathematical) ones, this so called “challenge” grows exponentially. In this paper, we analyze the impact of introducing and supporting some Math contents through video lectures, in a voice-over presentation style, based on animated arrangements, in our own mother language. These videos were developed for a first-year Math course in several Management degrees in the Tourism and Hospitality Area. The specific curricular items were chosen with a primary objective of trying to level up the mathematical competencies that are fundamental to the development of ‘mathematical literacy’ of our students. Our video lectures are available to students in our institutional Moodle platform, with all its features, along with other resources (as texts and proposed exercises) as well as in a YouTube channel. We will also describe students’ background areas of study in pre-university level and analyze if this has any influence in the way they interact with video-lectures in their own learning development and knowledge construction and report student’s perception of the eventual benefits of using this digital resource in engaging and promoting their self-responsibility in the learning process. Finally, we will analyze students’ evaluation of the videos recorded by the professors and uploaded to the Moodle platform and YouTube as a learning tool.